Soil salinity variations and cotton growth under long-term mulched drip irrigation in saline-alkali land of arid oasis - Wenhao Li; Zhenhua Wang; Jinzhu Zhang; Rui Zong (Irrigation Science, 2022)
The sustainable development and utilization of saline-alkali land are closely related to holding fast the minimum cultivated land area of China. The change of soil salt in cotton field under long-term mulched drip irrigation (MDI) is connected with the development of the national cotton industry. From 2015 to 2019, five cotton fields with different applying years of MDI, which were reclaimed in 2004, 2008, 2010, 2012 and 2015 respectively and were saline-alkali wasteland before, were monitored continuously in the Manas River irrigation area of Xinjiang. By means of continuous location monitoring and spatial–temporal variability (For example, the monitoring data of cotton fields under MDI in 2004, 2008, 2010, 2012 and 2015, and in the year of 2015 were counted as 12, 8, 6, 4 and 1 years, respectively), the spatial–temporal variations of soil salt and ions in cotton field with 1-16a MDI technology were presented. The cotton growth characteristics and its main influencing factors were also analyzed in the study. The results showed that saline-alkali cotton field experienced changed from intensive saline soil to moderate saline soil and finally to non-saline soil under long-term MDI. The change of soil salt and the response of cotton growth to soil salt were divided into three typical stages. Firstly, soil desalinated rapidly in 1-4a MDI cotton field, which the annual average desalination rate was 24.93% in 0–100 cm soil layer (root zone). Additionally, the survival rate of cotton rocketed from 1.48% to 42.04%, and yield increased sharply from 72.43 kg ha −1 to 3075.90 kg ha −1 . Soil desalination was lower in 5-11a MDI cotton field, which the annual average desalination rate was 10.92% at the root zone. The annual survival rate and yield of cotton increased by 6.26% and 5.18%, respectively. After 12a MDI, the soil salt in cotton field tended to be generally constant, which the average salt content in root zone was less than 2.49 g kg −1 . The survival rate of cotton was stable above 90.39%, and the yield per unit area exceeded 5401.32 kg ha −1 . Ions, sodium absorption ratio and Cl − and SO 4 2− equivalent ratio (CSER) in cotton soil also decreased with the extension of MDI. Salt composition changed year by year, but the type of intensive saline soil had always been chloride-sulphate solonchak (0.2 < CSER < 1). In practice, with a higher irrigation quota and ideal irrigation water quality, the soil salt environment of saline-alkali soil MDI cotton field had developed in favor of cotton growth in an oasis irrigation area. However, this management practice caused between 124.21–143.61 mm of water resources waste. Therefore, we should further enhanced the consciousness of water-saving and implemented quota management in practice.